The Ontology of Digital Literacy in Evaluating the Credibility of Internet-Based Learning Resources for Elementry School Students - Nurhidayah Nasution; Nurhayati Ritonga; Rini Handayani; Ifrah Muliyani E pulungan; Pahri Siregar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article is motivated by the increasing use of the internet as a learning resource for elementary school students who do not yet fully possess the ability to evaluate the accuracy of information. Ontologically, digital literacy is not only understood as the technical ability to use devices, but also as a critical awareness of the nature of information, its sources, and its validity. The purpose of this study is to analyze the concept of the ontology of digital literacy in helping elementary school students assess the accuracy of information from internet-based sources. The method used is qualitative research with a Systematic Literature Review (SLR) approach. Data were obtained from scientific journals, books, and relevant educational policy documents. The results show that ontology-based digital literacy emphasizes an understanding of the existence of information, its origins, and the criteria of truth involving aspects of logic, source credibility, and information context. These findings indicate that students equipped with ontological understanding tend to be more critical in distinguishing between hoax and factual information. The conclusion of this study is that the integration of an ontological approach in digital literacy is essential for developing critical thinking skills from an early age. The implication is that teachers need to develop learning strategies that not only focus on the use of technology but also on the critical evaluation of digital information